2013
DOI: 10.1016/j.bpj.2013.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Macro- to Microscale Strain Transfer in Fibrous Tissues is Heterogeneous and Tissue-Specific

Abstract: Mechanical deformation applied at the joint or tissue level is transmitted through the macroscale extracellular matrix to the microscale local matrix, where it is transduced to cells within these tissues and modulates tissue growth, maintenance, and repair. The objective of this study was to investigate how applied tissue strain is transferred through the local matrix to the cell and nucleus in meniscus, tendon, and the annulus fibrosus, as well as in stem cell-seeded scaffolds engineered to reproduce the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 63 publications
6
84
0
Order By: Relevance
“…Fiber-reinforced soft tissues are exposed to large loads and deformations that are transmitted through their hierarchical extracellular matrix to both cells and their nuclei within (20), regulating numerous cellular processes and playing important roles in the formation, maintenance, and ultimately degeneration of these tissues. In the context of engineered replacements, it will be important to understand both the extent to which these macro-to-microscale deformations are recapitulated in the engineered constructs and the mechanoresponsiveness of the cell types used in the fabrication of these constructs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiber-reinforced soft tissues are exposed to large loads and deformations that are transmitted through their hierarchical extracellular matrix to both cells and their nuclei within (20), regulating numerous cellular processes and playing important roles in the formation, maintenance, and ultimately degeneration of these tissues. In the context of engineered replacements, it will be important to understand both the extent to which these macro-to-microscale deformations are recapitulated in the engineered constructs and the mechanoresponsiveness of the cell types used in the fabrication of these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are widely used in these types of applications (4), and it is well established that they respond to mechanical signals in a manner that is dependent on a contractile cytoskeleton (1,2). As with native tissue cells, nuclei within MSCs also undergo marked deformations with applied tensile stretch (20,23,24). In this study, we found that the presence of a patent actin cytoskeleton, the tension within this cytoskeletal network, and the connections it makes to the nucleus through nesprin 1 giant, regulate the transmission of strain to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 3-D approach is unique because it considers out-ofplane motion, which can occur from misalignment with the uniaxial loading direction or anisotropy. 2-D methods have been used extensively to quantify strain transfer from the macro to microscales (Han et al, 2013; Upton et al, 2008), but many studies acknowledge that results are confounded by artifacts from excluding the effect of strain in the third dimension. Our matrix strain and cell deformation methods capture the 3-D microstructural response and how cells reorient or deform multi-dimensionally, providing a comprehensive picture of the strain environment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the ability to identify and quantify mesoscale architecture is important in other physical systems more broadly. The brain [56,62,[72][73][74] and biomaterials [75][76][77][78][79] are a few examples of systems where intermediate structure is crucial to function.…”
Section: Discussion and Methodological Considerationsmentioning
confidence: 99%